PENGARUH PENDIDIKAN, PEKERJAAN, PENDAPATAN DAN HARGA PRODUK TERHADAP TINGKAT KONSUMSI ROKOK DI KECAMATAN SUKOLILO - Permadi, Angga Dwi; Suparta, I Made (widya balina, 2025)
This study aims to analyze the effect of education level, occupation, income and product price on the level of cigarette consumption in Sukolilo District, Surabaya City. The type of research used is quantitative method. The data sources used are primary data obtained from distributing questionnaires to respondents of people who actively smoke in Sukolilo District and secondary data obtained from the Central Statistics Agency (BPS) and related agencies. The method of analysis used in this study is multiple linear regression analysis with the help of the SPSS for windows program version 25.0. The population and sample in this study were 81 respondents selected using non probability sampling technique, namely accidental sampling using Isac Michel formula with 10% margin of error. Data analysis was carried out using multiple linear regression, F test, T test, and coefficient of determination (R Square). The results showed that partially education, employment, income and product prices had a positive and significant effect on the level of cigarette consumption and the coefficient of determination was 89.2%. It is hoped that this information can provide benefits to the community in Sukolilo Subdistrict or can be input for local governments and policy makers in efforts to control cigarette consumption.